2016
DOI: 10.1364/boe.7.000399
|View full text |Cite
|
Sign up to set email alerts
|

Fast interferometric second harmonic generation microscopy

Abstract: We report the implementation of fast Interferometric Second Harmonic Generation (I-SHG) microscopy to study the polarity of non-centrosymmetric structures in biological tissues. Using a sample quartz plate, we calibrate the spatially varying phase shift introduced by the laser scanning system. Compensating this phase shift allows us to retrieve the correct phase distribution in periodically poled lithium niobate, used as a model sample. Finally, we used fast interferometric second harmonic generation microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Further, it was shown that the number of fibrils with different polarity in the tissue is equal . This behavior was also observed with interferometric SHG microscopy of collagenous tissues . Hence, we favor the third explanation.…”
Section: Resultssupporting
confidence: 74%
“…Further, it was shown that the number of fibrils with different polarity in the tissue is equal . This behavior was also observed with interferometric SHG microscopy of collagenous tissues . Hence, we favor the third explanation.…”
Section: Resultssupporting
confidence: 74%
“…42). In short, the excitation source was a mode-locked Ti:Sapph laser (810 nm wavelength, 80 MHz repetition rate, ~150 fs pulses width, Tsunami, Spectra Physics) pumped by a 12 W Millenia Pro laser (Spectra Physics).…”
Section: Methodsmentioning
confidence: 99%
“…For a complete description of the I-SHG method and SHG set-up we refer to [23]. Importantly, an air immersion objective (UplanSApo 20X, NA 0.75, Olympus, Japan)) was used for excitation and the SHG emission was then collected with a 0.8NA objective (LUMPlanFLN, 40X, Olympus) to ensure that the numerical aperture is sufficiently high to collect the whole radiation pattern.…”
Section: Shg and I-shg Microscopymentioning
confidence: 99%
“…tures of Periodicall ation of domains o n be focused inside II) leading to a ch f myosin inside the bands (with no m H-zone, located in filaments lead The dips correspo lack of myosin ( nds of opposite po ructive interferenc he number of mini rved in SHG micro some extent sim rity [19] [23]. In this m nventional SHG ures are always χ (2) , where χ (2) ved in the inte e interferences tendon, other fficult to extrac e is a periodic own to have cr ls [28,29], whe non-negligible on, which caus Niobate (PPLN, A y.…”
Section: Introductionmentioning
confidence: 99%